On a singular semilinear elliptic problem with an asymptotically linear nonlinearity. Issue 1 (February 2016) - Anello, Giovanni; Faraci, Francesca
Abstract : In this paper we deal with a singular elliptic problem involving an asymptotically linear nonlinearity and depending on two positive parameters. We investigate the existence, uniqueness and non-existence of the minima of the functional associated with the problem and, by employing a natural and very general definition of a weak solution, we also obtain a bifurcation-type result.